2017
DOI: 10.2147/copd.s131246
|View full text |Cite
|
Sign up to set email alerts
|

Association between <em>RTEL1</em> gene polymorphisms and COPD susceptibility in a Chinese Han population

Abstract: ObjectiveWe investigated the association between single-nucleotide polymorphisms in regulation of telomere elongation helicase 1 (RTEL1), which has been associated with telomere length in several brain cancers and age-related diseases, and the risk of chronic obstructive pulmonary disease (COPD) in a Chinese Han population.MethodsIn a case–control study that included 279 COPD cases and 290 healthy controls, five single-nucleotide polymorphisms in RTEL1 were selected and genotyped using the Sequenom MassARRAY p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Of 207 proteins detected with the SOMAscan 1.3 K platform, 81 (41%) have previously been detected in BALF [ 29 ]. Using 1323 uniquely mapped SOMAscan protein identities as reference/background gave at hand that the 207 proteins detected in PEx samples are enriched 5.9 times with the proteins previously detected in supernatant from BALF samples (p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…Of 207 proteins detected with the SOMAscan 1.3 K platform, 81 (41%) have previously been detected in BALF [ 29 ]. Using 1323 uniquely mapped SOMAscan protein identities as reference/background gave at hand that the 207 proteins detected in PEx samples are enriched 5.9 times with the proteins previously detected in supernatant from BALF samples (p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to lung structural effects, RNA-sequencing revealed that the lung genes dysregulated by the in utero SHS plus elastase treatment ( Figure 4A ) were consistent with emphysema pathogenesis ( Kneidinger et al, 2011 ). The up-regulated genes included: centrosomal protein 57 ( Cep57 ; 6.3-fold), a gene identified as part of a network module associating in utero SHS exposures with adult COPD in humans ( Kachroo et al, 2020 ); nuclear receptor coactivator 7 ( Ncoa7 ; 7.0-fold), whose expression was dysregulated in COPD lung tissue compared to non-disease tissue ( Cho et al, 2015 ); nuclear factor of activated T cells 2 ( Nfatc2 ; 7.9-fold), a transcription factor involved in T cell cytokine production, whose dysregulation has been associated with the pathogenesis of COPD exacerbation ( Singh et al, 2014 ); regulator of telomere elongation helicase 1 ( Rtel1 ; 8.6-fold), for which it was demonstrated that a single-nucleotide polymorphism in this gene was associated with COPD in a case-control study ( Ding et al, 2017 ); and leucine rich repeats and immunoglobulin like domain 2 ( Lrig2 ; 4.8-fold), for which a single-nucleotide polymorphism near this gene was associated with alterations in adjusted density of emphysematous lungs in a genome-wide association study ( Kim et al, 2019a ; Figure 4A ). We also found ( Figure 4A ) that the gene expression of wingless-type MMTV integration site family member 7B ( Wnt7b ) was down-regulated (-9.2-fold) in the in utero SHS plus adult elastase-treated female mice compared to the in utero air plus adult elastase group.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we investigated six SNPs in RTEL1: rs6089953, rs6010620, rs6010621, rs2297440, rs4809324, and rs2297441. Among these SNPs, Ding Y et al, (Ding et al, 2017) reported the presence of rs4809324 was associated with increasing the COPD risk. The presence of rs2297441 was found to be associated with Crohn's disease in Canadian children (Amre et al, 2009).…”
Section: Discussionmentioning
confidence: 99%